2018
DOI: 10.1111/epi.14072
|View full text |Cite
|
Sign up to set email alerts
|

Does bilingualism increase brain or cognitive reserve in patients with temporal lobe epilepsy?

Abstract: Despite poorer integrity of regional frontal lobe WM, bilingual patients performed similarly to monolingual patients and HC on EF measures. These findings align with studies suggesting that bilingualism may provide a protective factor for individuals with neurological disease, potentially through reorganization of EF networks that promote greater cognitive reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Despite the fact that all these studies report worse preserved brain in bilinguals compared to monolinguals, both in terms of grey and white matter structure (Duncan, Nikelski, Pilon, Steffener, Chertkow & Phillips, 2018;Gold, Kim, Johnson, Kryscio & Smith, 2013;Schweizer, Ware, Fischer, Craik & Bialystok, 2012), in all cases the bilingual groups matched or even outperformed the monolingual groups in cognitive tests, suggesting more efficient recruitment of the spared brain tissue in the former group. It is worth mentioning that a similar pattern (i.e., higher diffusivity but equal cognitive abilities) has also been reported in bilingual patients with temporal lobe epilepsy when compared to monolinguals matched on diagnosis (Reyes, Paul, Marshall, Chang, Bahrami, Kansal, Iragui, Tecoma, Gollan & McDonald, 2018). However, and despite some behavioural evidence, little is known about how bilingualism interacts with other neurodegenerative diseases, such as Parkinson's, Huntington's, Primary Progressive Aphasia and Multiple Sclerosis (for a review, see Voits, Robson, Rothman & Pliatsikas, in preparation); for example, a recent study with bilingual patients with Huntington's disease showed that the amount of usage of two languages predicted higher GM volume in the right IFG, although in the absence of a control group it is hard to tell whether this is a generic effect of bilingualism or an effect specific to this patient group (Martínez-Horta, Moreu, Perez-Perez, Sampedro, Horta-Barba, Pagonabarraga, Gomez-Anson, Lozano-Martinez, Lopez-Mora, Camacho, Fernández-León, Carrió & Kulisevsky, 2018).…”
Section: Bilingualism and Disease-related Neurodegenerationsupporting
confidence: 69%
“…Despite the fact that all these studies report worse preserved brain in bilinguals compared to monolinguals, both in terms of grey and white matter structure (Duncan, Nikelski, Pilon, Steffener, Chertkow & Phillips, 2018;Gold, Kim, Johnson, Kryscio & Smith, 2013;Schweizer, Ware, Fischer, Craik & Bialystok, 2012), in all cases the bilingual groups matched or even outperformed the monolingual groups in cognitive tests, suggesting more efficient recruitment of the spared brain tissue in the former group. It is worth mentioning that a similar pattern (i.e., higher diffusivity but equal cognitive abilities) has also been reported in bilingual patients with temporal lobe epilepsy when compared to monolinguals matched on diagnosis (Reyes, Paul, Marshall, Chang, Bahrami, Kansal, Iragui, Tecoma, Gollan & McDonald, 2018). However, and despite some behavioural evidence, little is known about how bilingualism interacts with other neurodegenerative diseases, such as Parkinson's, Huntington's, Primary Progressive Aphasia and Multiple Sclerosis (for a review, see Voits, Robson, Rothman & Pliatsikas, in preparation); for example, a recent study with bilingual patients with Huntington's disease showed that the amount of usage of two languages predicted higher GM volume in the right IFG, although in the absence of a control group it is hard to tell whether this is a generic effect of bilingualism or an effect specific to this patient group (Martínez-Horta, Moreu, Perez-Perez, Sampedro, Horta-Barba, Pagonabarraga, Gomez-Anson, Lozano-Martinez, Lopez-Mora, Camacho, Fernández-León, Carrió & Kulisevsky, 2018).…”
Section: Bilingualism and Disease-related Neurodegenerationsupporting
confidence: 69%
“…Learning another language was identified as contributing to cognitive reserve, mainly in relation to overall cognitive function. It was observed that learning another language has an impact on brain structure, in that people need to select a language or communicate, which involves executive function capacity, cognitive control, and cognitive flexibility (Dasha et al, 2017;Reyes et al, 2018). In addition, it can be considered that this activity protects against symptoms of dementia in older adults (Bialystok et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Major white matter tracts across the brain were labeled using the well-established probabilistic fiber tract atlas, AtlasTrack (Gustavson et al, 2019; Hagler et al, 2009; Hagler et al, 2019; Kaestner et al, 2020; Reyes et al, 2018; Ursache et al, 2016). More specifically, subjects’ T1-weighted MRI images were first registered nonlinearly to the atlas.…”
Section: Methodsmentioning
confidence: 99%